Effect of the combination of naa, kinetin and sucrose on the induction of somatic embryogenesis in lulo (solanum quitoense lam.) (2014)
Lulo is a species of great importance to the fruticulture of Colombia, but has significant phytosanitary problems that require an aggressive breeding program oriented toward the production of genotypes with tolerance to phytopathogens. These programs need to establish highly efficient mass plant propagation protocols, such as somatic embryogenesis. This study focused on research on the somatic embryogenesis of lulo using kinetin, naphthalene acetic acid-NAA (Plant Growth Regulators, PGRs), and different sucrose concentrations in a MS medium. Two lulo varieties, Solanum quitoense var. septentrionale and S. quitoense var. quitoense, and two explant types (hypocotyl and cotyledon) were used, incubated in dark conditions at 25±2°C. The highest production percentage of the embryos was obtained when 50 μM of NAA were added to the medium with sucrose (50.0 and 263.1 μM) for the two explant types used. In lulo with spines, the highest percentage of embryonic structures (50%) was observed with cotyledonary leaf explants and 50 μM of NAA; while in the spineless lulo, the embryonic structures were observed in the same type of explant with 50 μM of NAA + 263.1 μM of sucrose (32%).